Formulation optimization and in vitro evaluation for the gastro retentive tablets of Labetolol - Sravanthi Todasam; Nagarajan Srinivasan (International Journal of Pharmacy and Analytical Research, 2016)
The controlled gas tric retention of s olid dos age forms may be achieved by the mechanis ms of mucoadhes ion, flotation, sedimentation, expans ion, modified s hape s ystems , or by the s imultaneous adminis tration of pharmacological agent that delay gas tric emptying. Bas ed on thes e approaches , clas s ification of floating drug delivery s ystems (FDDS) has been des cribed in detail. Floating granules we re p re p a re d by us ing Dire c t Compres s ion technique. The oral bioavailabilty of Labetolol has been reported to be about 25%. Gas tric floating drug delivery is one approach where the gas tro intes tinal res idence time is prolonged becaus e of the floating behavior. In the pres ent study the formulations were prepared by us ing different proportions of polymer. The prepared formulations were evaluated for different phys icochemical characteris tics s uch as thicknes s and diameter, drug content, weight variation, hardnes s , friability. The releas e c h a ra c t e ris t ic s of the formulation were s tudied in in-vitro conditions . The IR s pectrum of pure drug and drug-polymer mixture revealed that there was no interaction between polymer and drug. The prepared floating tablet is indus trially feas ible method. Bulk dens ity and tapped dens ity s hown good packability and Ca rr’s index res ults s hown excellent compres s ibility. Formulation F16 containing combination of Metalos e SR and Manucol was found to releas e a maximu m of 97.2431% at the 12th hour.